Analisis Penggunaan Dana Desa di Negeri Ihamahu - Mona O J Joseph; Markus J Pattinama; Junianita F Sopamena (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This study aims to find out how the village fund is utilized in agricultural and fishery business activities. The research method used a survey by deliberately choosing 25 respondents from 84 populations. Data collection was carried out through interviews equipped with a questionnaire tool. Data analysis was carried out qualitatively-descriptively. The results showed that 68% of the process of channeling aid funds was on target and 32% was not on target. Most of the people who received assistance were dissatisfied because it did not match the amount they expected. Respondents responses to village aid funds were as follows: very helpful (28%), quite helpful (16%) and the rest didn t help at all (56%). The provision of assistance that was misdirected occurred because the government did not conduct a needs analysis survey before providing assistance to the target group and there was no evaluation after the distribution of the village fund.